Screening for thyroid dysfunction during the second trimester of pregnancy. (9th September 2013) - Qian, Wei; Zhang, Lijun; Han, Mi; Khor, Shuzin; Tao, Jun; Song, Mengfan; Fan, Jianxia
Abstract: The primary objective of this study is to explore the influence of different screening strategies on the prevalence of thyroid dysfunction and the missed diagnosis during pregnancy. A total of 1889 pregnant women (13–27 weeks) were divided into high-risk and low-risk groups according to the backgrounds of them collected by questionnaire. We detected the prevalence of thyroid dysfunction in high-risk groups and low-risk pregnant women by normal reference range during the second trimester in our research. High-risk groups accounted for 10.69% of all the pregnant women in this study. Using targeted high-risk case screening strategy, misdiagnosis rate of pregnancy with hyperthyroidism, subclinical hyperthyroidism, pregnancy with hypothyroidism, subclinical hypothyroidism, low T4 syndrome and positive TPOAb were 87.5% (14 cases), 87.08% (155 cases), 87.08% (155 cases), 83.93% (47 cases), 89.47% (17 cases) and 88.35% (91 cases), respectively. Furthermore, there was no statistically significant difference between high-risk group and low-risk group in the prevalence of thyroid dysfunction. Therefore, we believe that universal screening to pregnant women can effectively reduce misdiagnosis rate of thyroid dysfunction. Further, we recommend universal screening for thyroid function in second trimester of pregnancy.